A serious leisure perspective of culinary tourism co-creation: the influence of prior knowledge, physical environment and service quality. Issue 7 (5th June 2020) - Prayag, Girish; Gannon, Martin Joseph; Muskat, Birgit; Taheri, Babak
Abstract : Purpose: Recognising tourists' increasing desire for authentic destination-specific experiences, the hospitality industry has responded by increasing provision of innovative culinary activities. This study aims to use the concepts of serious leisure and terroir to examine how knowledge, physical environment and service quality influence co-creation within the culinary tourism context. Design/methodology/approach: Following cooking class participation, 575 domestic Iranian tourists were surveyed. These educational classes provide opportunities to learn about local foods alongside peers in an interactive setting. Consistent with the benefits of serious leisure, this consumption context could prove conducive to stimulating co-creation. Findings: Prior knowledge strongly influences tourists' reflective and recreational motives for participation (i.e. the benefits of serious leisure). This shapes how tourists evaluate physical environments and service quality therein; influencing value co-creation and supporting serious leisure as the conceptual lens through which to understand experiential culinary consumption. Research limitations/implications: The proposed conceptual model was tested on domestic tourists following class participation. However, in suggesting that visually-stimulating, tactile premises with the olfactory appeal can encourage co-created experiences, the findings are relevant to service touch-point management more generally. Originality/value: Recognizing the influential role played by the physical and social aspects of experiential consumption, the serious leisure framework improves an extant understanding of value co-creation.